Fertigation with silicon in rose varieties on severity of powdery mildew (Sphaerotheca pannosa var. rosae) - Albornoz B., Cesar; Silva P., Amanda; Torres M., Francisco (Revista de Ciencias Agrícolas, 2016)
The research evaluated the Fertigation with silicon in the severity of the powdery mildeo (Sphaerotheca pannosa var. Rosae) in three varieties of rose under greenhouse. The experiment was a split-split plot design with silicon doses (DS) as the main-plot factor: (DS1 = 3mgL-1), (DS2 = 6mgL-1) and (DS3 = 9mgL- 1); Fertigation (L) as the sub-plot factor: (L1 = 3 mm day-1), (L2 = 5 mm day-1) and rose varieties (V) as the sub-sub-plot factor: (V1 = Vendela), (V2 = Reed Unique) and (V3 = Miracle). There were differences (p≤0.01) due to the effect of SD (silicon dose), L (fertigation) and V (varieties); As well as the DS * L interaction (p≤0.01). DS3 applications reduced fungus severity (20%) while DS1 was less efficient (230%). Lower percentages of fungal severity were obtained with Fertigation L1 (130%) and while L2 had the higher (280%). Varieties V2 and V3 were less affected by fungus (170 and 160%) while V1 was more susceptible to it (320%). The DS3 dose and the L1 fertigation interaction reduced fungal severity (75%) (p≤0.05). The behavior of the Miracle and Reed Unique rose varieties with a 3-mm.day-1 fertigation and a silicon dose of 9mgL-1 could be key to decreasing the severity of Sphaerotheca pannosa var. Rosae in flower growing areas of Colombia.